38th Fluid Dynamics Conference and Exhibit 2008
DOI: 10.2514/6.2008-3735
|View full text |Cite
|
Sign up to set email alerts
|

Starting Issues and Forward-Facing Cavity Resonance in a Hypersonic Quiet Tunnel

Abstract: AFOSR/NA Unclassified and Approved for Public Release M.S. thesis by Rodrigo Segura with development of LDI for Mach-6 quiet tunnel and measurements in Mach-4 quiet tunnel Laminar-turbulent transition is a pivotal factor for the design of hypersonic vehicles but the mechanisms that induce transition are not well understood. A laser differential interferometer (LDI) is a non-intrusive optical device that measures the optical path length difference between two laser beams. The LDI is a reliable calibrated instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Several methods were used to control separation of the nozzle-wall boundary layer caused by the diffuser section and its various inserts [28]. This separation was visible as a large low-frequency oscillation that occurred simultaneously on the signals from the probe and the wall hot films.…”
Section: Apparatus For Pitot and Hot-wire Probe Measurementsmentioning
confidence: 99%
“…Several methods were used to control separation of the nozzle-wall boundary layer caused by the diffuser section and its various inserts [28]. This separation was visible as a large low-frequency oscillation that occurred simultaneously on the signals from the probe and the wall hot films.…”
Section: Apparatus For Pitot and Hot-wire Probe Measurementsmentioning
confidence: 99%
“…A decrease of the maximum quiet conditions of the Mach 4 quiet tunnel during the 2000s forced Juliano et al to test their cavity model at lower freestream pressures than Ladoon et al [13]. It is interesting to also note that Ladoon et al tested cavity depths ranging from L∕D 0.272 to 1.984 and could not find the critical depth [13,14]. It is unclear why Ladoon et al [13] was unable to determine the critical depth using the same method as Juliano et al [14].…”
mentioning
confidence: 99%
“…In the late 2000s, Juliano et al [14] found the critical depth for a similar model in the same facility as used by Ladoon et al [13]. Juliano et al [14] adjusted the L∕D from 0.5 to 3.0, and pressure fluctuations were compared for each depth tested in the experiment.…”
mentioning
confidence: 99%
See 2 more Smart Citations